An allosteric disulfide bond is involved in enhanced activation of factor XI by protein disulfide isomerase. (20th October 2016) - Zucker, M.; Seligsohn, U.; Yeheskel, A.; Mor‐Cohen, R.
Abstract : Essentials Reduction of three disulfide bonds in factor (F) XI enhances chromogenic substrate cleavage. We measured FXI activity upon reduction and identified a bond involved in the enhanced activity. Reduction of FXI augments FIX cleavage, probably by faster conversion of FXI to FXIa. The Cys362‐Cys482 disulfide bond is responsible for FXI enhanced activation upon its reduction. Summary: Background: Reduction of factor (F) XI by protein disulfide isomerase (PDI) has been shown to enhance the ability of FXI to cleave its chromogenic substrate. Three disulfide bonds in FXI (Cys118–Cys147, Cys362–Cys482, and Cys321–Cys321) are involved in this augmented activation. Objectives: To characterize the mechanisms by which PDI enhances FXI activity. Methods: FXI activity was measured following PDI reduction. Thiols that were exposed in FXI after PDI reduction were labeled with 3‐( N ‐maleimidopropionyl)‐biocytin (MPB) and detected with avidin. The rate of conversion of FXI to activated FXI (FXIa) following thrombin activation was assessed with western blotting. FXI molecules harboring mutations that disrupt the three disulfide bonds (C147S, C321S, and C482S) were expressed in cells. The antigenicity of secreted FXI was measured with ELISA, and its activity was assessed by the use of a chromogenic substrate. The effect of disulfide bond reduction was analyzed by the use of molecular dynamics. Results: Reduction of FXI by PDI enhanced cleavage of both its chromogenic substrate, S2366, and its physiologic substrate, FIX, and resulted in opening of the Cys362–Cys482 bond. The rate of conversion of FXI to FXIa was increased following its reduction by PDI. C482S‐FXI showed enhanced activity as compared with both wild‐type FXI and C321S‐FXI. MD showed that disruption of the Cys362–Cys482 bond leads to a broader thrombin‐binding site in FXI. Conclusions: Reduction of FXI by PDI enhances its ability to cleave FIX, probably by causing faster conversion of FXI to FXIa. The Cys362–Cys482 disulfide bond is involved in enhancing FXI activation following its reduction, possibly by increasing thrombin accessibility to FXI.